(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The roving machine plays a crucial role in determining the quality of ring-spun yarn by influencing fibre alignment, drafting behaviour, and twist uniformity before final spinning. Variations in roving twist, tension, and winding density directly impact yarn evenness, hairiness, and tensile properties. This paper analyses how the roving machine affects the ring spinning process and proposes guidelines for optimizing key parameters. Results from previous studies and industrial data demonstrate that stable roving tension and optimal twist levels improve yarn strength and reduce end-breakage rates, contributing to higher production efficiency and yarn consistency.